The Impact of Religious Coping Mechanisms on Mental Health Outcomes among Individuals in Uganda: A Desk Review of Qualitative Secondary Data - Judith Arinaitwe; Arthur Ahumuza; Israel Mwebembezi; Syson Amutuhaire (East African Journal of Arts and Social Sciences, 2026)
Mental health disorders are a growing global public health concern, with low- and middle-income countries facing significant treatment gaps due to limited mental health resources. In Uganda, religion plays a central role in shaping health beliefs, coping behaviours, and help-seeking practices. Consequently, religious coping mechanisms have emerged as important resources for managing psychological distress and promoting well-being. This study examined the impact of religious coping mechanisms on mental health outcomes among individuals in Uganda through a qualitative desk review of secondary data. A qualitative desk review design was used to synthesise evidence from peer-reviewed journal articles, policy documents, institutional reports, and literature published between 2010 and 2026. Literature was retrieved from electronic databases, including PubMed, Scopus, PsycINFO, Web of Science, Google Scholar, and African Journals Online. Data were analysed using reflexive thematic analysis informed by Religious Coping Theory. The review identified four major themes. First, positive religious coping strategies, including prayer, meditation, scripture reading, participation in religious activities, and seeking spiritual guidance, were associated with reduced anxiety and depressive symptoms, enhanced resilience, improved emotional regulation, and increased subjective well-being. Second, faith communities and religious leaders provided essential sources of social, emotional, and spiritual support, particularly in underserved settings. Third, negative religious coping such as attributing mental illness to divine punishment, curses, or demonic influence was associated with increased psychological distress, stigma, and delayed utilisation of formal mental health services. Finally, the findings highlighted the need for stronger collaboration between mental health systems and faith-based organisations to promote culturally responsive care. The study concluded that religious coping mechanisms exert both protective and detrimental effects on mental health outcomes among individuals in Uganda. Integrating positive religious coping into mental health promotion strategies while addressing harmful religious beliefs may enhance the accessibility, acceptability, and effectiveness of mental health care services in Uganda.